Evaluation of User Satisfaction on the Indonesian National Police Recruitment Website Using the EUCS Method - Dwi Pratiwi, Dinda Malika; Sanglise, Marlinda; Baisa, Lorna Yertas (Journal of Applied Informatics and Computing, 2025)
The digitalization of public services encourages government institutions to provide efficient and responsive information systems, including in the recruitment process of the Indonesian National Police (Polri). The Polri recruitment website was developed as an online registration platform to improve transparency, accessibility, and service effectiveness. However, systematic evaluations of user satisfaction with this website are still limited. This study aims to measure user satisfaction using the End User Computing Satisfaction (EUCS) model. A quantitative approach was applied, with data collected through questionnaires from 144 prospective applicants in the West Papua Regional Police area. Data were analyzed using the Partial Least Squares - Structural Equation Modelling (PLS-SEM) method. The findings reveal that ease of use and timeliness significantly influence user satisfaction, while content, accuracy, and format do not. This indicates that usability and information timeliness play a more critical role. The study encourages system developers to focus on enhancing functional and responsive features to improve digital public services.